The Church of Ireland primary school in an expanding educational marketplace: the use of school websites to promote school identity and ethos. Issue 1 (2nd January 2021) - Wilkinson, Jacqueline
Abstract : Church of Ireland primary schools account for 5% of the total of primary schools in the Republic of Ireland. With the growing demand for non-religious schools in the educational marketplace it is becoming more important that each one of this small cohort of schools looks at its self-identity, and what it offers in terms of a distinctive ethos to students and parents. This paper is based on desk-based research conducted in 2018, focussed on the websites of 74% of Church of Ireland primary schools. The study found that 35% of these schools do not make it clear that they are Church of Ireland schools on the home page of their websites. By using content analysis methodologies to analyse ethos statements on the school websites, it was found that schools were very dependent on a sample ethos document issued in 2003, and beyond that there was little consistency in the narrative of what the ethos of a Church of Ireland primary school might look like. The study, whilst noting that all schools are unique, recommends conversation about ethos so that schools are equipped and supported in the development of their distinct identity as Church of Ireland primary schools within a changing educational marketplace.